A Conceptual Study on Meda Vikara and the Applied Aspects of Udvartana with Reference to “Udvartanam Kaphaharam Medash Prabilayanam” by Certain Drugs - Pradhan, Subhrakanta; Sahoo, Manoj Kumar; Dash, Biswajit (International Research Journal of Ayurveda & Yoga, 2023)
Background: Sthoulya (obesity) is such a disease which provides the platform for so many hazards such as hypertension and diabetes mellitus as well as psychological disorders such as stress. The mortality and morbidity rates are higher in obese persons. It is one of the most common, yet among the most neglected public health problems in the present world. Materials and Methods: Thirty patients were taken for the study and all patients were divided into two equal groups, that is, Group A and Group B. Group A: 15 patients were given Guduchyadi Churna Udvartana for 15 days. Group B: 15 patients were given Guduchyadi Churna Udvartana along with internal use of the same churna for 15 days. A comparison was done between Group A and Group B and the assessment was made before and after treatment. Result and Discussion: During the entire duration of therapy, there was not any adverse/untoward effect or adverse drug reactions observed for both the trial groups. Here, Group B showed better result in overall total parameters. Conclusion: The effect of the medicine, that is, Guduchyadi Churna is more significant in reducing the subjective and objective parameters and significant in reducing the elevated lipids (serum cholesterol, LDL, and triglycerides) and elevating the HDL.